The mediation and interaction of depressive symptoms in activities of daily living and active aging in rural elderly: A cross-sectional survey - Fu, Xuelian; Su, Yinli; Zeng, Chunyan; Liu, Liqiong; Guo, Yang; Wu, Yuanyuan (Frontiers in Public Health, 2022)
Background: Compared with urban areas, old adults in rural areas have limited access to medical and health resources in China. Active of daily living ability (ADL) decline and depressive symptoms are common in rural older adults. In particular, the depressive symptoms of the elderly in rural areas are often ignored. Thus, it is difficult to realize high-level active aging at the individual level. In order to explore the effects of ADL and depressive symptoms on the active aging of rural elderly, we conducted a survey and analyzed the mediation and interaction effects of depressive symptoms of ADL on active aging. Methods: From July to November 2019, a cross-sectional study of 945 elderly rural individuals was conducted in three townships in Xiangtan County, China. Active aging, ADL, and depressive symptoms were assessed using the positive aging questionnaire (PAEQ), ADL scale, and depression in old age scale (DIA-S), respectively. PROCESS macro program model 4 and logistic regression were used to explore the mediation and interaction between ADL and depressive symptoms on active aging. Results: The rates of ADL decline and depressive symptoms were 44.7% and 19.7%, respectively. Mediated effect analysis showed that the relationship between ADL and active aging could be partly mediated by depressive symptoms. Logistic regression showed that ADL and depressive symptoms have an interactive additive effect on active aging. The relative excess risk of interaction (RERI), the attributable proportion due to interaction (API), and the synergy index (SI) scores were 13.109, 0.621, and 2.871, respectively. Older adults with ADL decline and depressive symptoms had higher (OR=21.115) odds of well-below-average active aging compared with older adults with ADL decline (OR=3.258) or only depressive symptoms (OR=5.749). Conclusion: The findings suggest that the association between ADL and active aging is persistent and partly mediated by depressive symptoms, and comorbid depressive symptoms and ADL decline have an additive effect on active aging. For the rural elderly with ADL decline and low-level active aging, we can promote the realization of high-level active aging at the individual level through the prevention and treatment of depressive symptoms based on multidisciplinary care.